Metastatic squamous cell carcinoma in the neck presenting with Horner syndrome - a cause of the condition not previously described. Issue 6 (July 2016) - Alam, Peyman; Sloane, James; Koraitim, Mohamed; Brennan, Peter A.
Abstract: Horner syndrome, a combination of pupillary miosis, ptosis and facial anhidrosis, results from damage to the oculosympathetic nerve pathways. It can occur anywhere from the hypothalamus to the eye, but to our knowledge, metastatic disease to a node in the neck from a mucosal squamous cell carcinoma (SCC) of the head and neck has not previously been reported as a primary cause in humans. It is surprising that it does not present more often given the frequency of metastatic disease in the neck. We discuss how it may have occurred, and highlight the importance of a thorough examination and investigation of the head and neck in patients who present with unusual neurological signs.